dowód:
<p:{AxB)c 3 f -*{ f,, f2)e AcXBc -bijekcja f :C -3 AxB
f:C —3 A (2\C -3B
niech:
BnC = 0=5ÓSjC~A“xAc dowód:
f: BuC—> A
f|.:B-»A
f|c:C-»A dowód:
(p: A8x0 * f —> hf e (AB)C - bijekcja
f: BxC ?(6,c) -> f{b,c)e A
g.t:B}b-* f(b,c)eA mech: „
niech:
:C3c-3g/ee A" >,,e[A’)C
(p - injekcja
fi- fi e A**:q>( f,)=<p( f2) <=» hfi = \ <=> VreC: hfl (c) = \ (c) <=> V„c : g,_, = g,; «• V„cVfc a: g t.c (b) = g,;, (b I » V„cVk , : f, (b, c) = f2 (b, c) « f, = f2 (p - surjekcja
bierzemy _ dowo ln e _ h e (A 8) h:C5c->h(c)e A8 =>/i(c): B 36 =>(/i(c))(6) € A niech: f: BxC 3(6,c) —»(/i(c))(6)e A=> f e A6*1 <P\ f)=h,e[A‘)'
h, =h<=>V„c:hf(c)=h(c) <=» V„c:gf c = h(c) <=> V„cVteB :gfc (b) =( /i(c))(6) ^ VreCV teB * f[b,c) =(/i(c))(b)
3m,b - injekcja 3Cc„: A ~ C dowód:
"3f.A_*B - injekcja => f: A—> f [ A] -bijekcja niech : C = f[A\cB=*C~A ^ 3CcB : A~C <=^ 3f:A-*c -bijekcja a C cB^ 3^.a_>b